Ways of Knowing Compassion: How Do We Come to Know, Understand, and Measure Compassion When We See It? - Mascaro, Jennifer S.; Florian, Marianne P.; Ash, Marcia J.; Palmer, Patricia K.; Frazier, Tyralynn; Condon, Paul; Raison, Charles (Frontiers in Psychology, 2020)
Over the last decade, empirical research on compassion has burgeoned in the biomedical, clinical, translational, and foundational sciences. Increasingly sophisticated understandings and measures of compassion continue to emerge from the abundance of multi- and cross-disciplinary studies. Naturally, the diversity of research methods and theoretical frameworks employed presents a significant challenge to consensus and synthesis of this knowledge. To bring the empirical findings of separate and sometimes siloed disciplines into conversation with one another requires an examination of their disparate assumptions about what compassion is and how it can be known. Here, we present an integrated theoretical review of methodologies used in the empirical study of compassion. Our goal is to highlight the distinguishing features of each of these ways of knowing compassion, as well as the strengths and limitations of applying them to specific research questions. We hope this will provide useful tools for selecting methods that are tailored to explicit objectives (methods matching), taking advantage of methodological complementarity across disciplines (methods-mixing), and incorporating the empirical study of compassion into fields in which it may be missing.